WiseBP: Mobile Application For Blood Pressure Monitoring - A Hamid, Rahayu; Yee, Ooi Kar (Applied Information Technology And Computer Science, 2020)
The prevalence of hypertension in Malaysia is increasing. Hence, awareness and control of hypertension is necessary. Generally, hypertension patients need to check-up regularly to keep track for their health care including blood pressure. However, doctor might not be able to always keep track on them and give them immediate feedback. Therefore, it can be helpful in diagnosing or monitoring high blood pressure if they record their readings in a blood pressure log electronically. WiseBP mobile application that let users to record blood pressure reading and the data is saved inside the application. They can view blood pressure chart to know which blood pressure categories they are. There are also reminder features and diet and exercise suggestions provided in this application. This mobile application is developed using Android Studio software and the methodology chosen for this project is Multimedia Mobile Content Development (MMCD). In short, WiseBP application is an Android based health self-monitoring application for hypertension patients to monitor their blood pressure with improved features to assist patients in self-managing their lifestyle.